2020
DOI: 10.1183/23120541.00701-2020
|View full text |Cite
|
Sign up to set email alerts
|

ICS-formoterol reliever versus ICS and short-acting β2-agonist reliever in asthma: a systematic review and meta-analysis

Abstract: BackgroundThe Global Initiative for Asthma recommends as-needed inhaled corticosteroid (ICS)-formoterol as an alternative to maintenance ICS plus short-acting beta2-agonist (SABA) reliever at Step 2 of their stepwise treatment algorithm. Our aim was to assess the efficacy and safety of these two treatment regimens, with a focus on severe exacerbation prevention.MethodsWe performed a systematic review and meta-analysis of all randomised controlled trials (RCTs) comparing as-needed ICS-formoterol with maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 30 publications
2
42
0
Order By: Relevance
“…This therapeutic approach is supported by the results of two pivotal 52-week, double-blind, randomized controlled trials, SYGMA 1 [18] and SYGMA 2 [19], in patients with mild asthma, and two open-label, 52-week studies in patients with mild-to-moderate asthma (PRACTICAL) [20] or mild asthma (Novel START) [21], as well as a complementary systematic review and meta-analysis [22]. SYGMA 1, SYGMA 2 and Novel START demonstrated a comparable annual rate of severe exacerbations between as-needed budesonideformoterol and twice daily budesonide maintenance (low-dose ICS) plus as-needed terbutaline (SABA), whereas the rate was significantly lower with as-needed budesonide-formoterol in the PRACTICAL study [20].…”
Section: Introductionmentioning
confidence: 96%
“…This therapeutic approach is supported by the results of two pivotal 52-week, double-blind, randomized controlled trials, SYGMA 1 [18] and SYGMA 2 [19], in patients with mild asthma, and two open-label, 52-week studies in patients with mild-to-moderate asthma (PRACTICAL) [20] or mild asthma (Novel START) [21], as well as a complementary systematic review and meta-analysis [22]. SYGMA 1, SYGMA 2 and Novel START demonstrated a comparable annual rate of severe exacerbations between as-needed budesonideformoterol and twice daily budesonide maintenance (low-dose ICS) plus as-needed terbutaline (SABA), whereas the rate was significantly lower with as-needed budesonide-formoterol in the PRACTICAL study [20].…”
Section: Introductionmentioning
confidence: 96%
“…A recent meta-analysis of all four studies found that as-needed budesonide–formoterol reduced the risk of emergency department visits for asthma by 35% compared with regular ICS plus as-needed SABA. 16 …”
Section: How Strong Is the Evidence For The New Recommendations?mentioning
confidence: 99%
“…• Second, although there is strong evidence to support the efficacy of the as-needed strategy, assessment of the underlying airway inflammation in asthma using fractional exhaled nitric oxide (NO) measurement showed higher levels of NO in mild asthma patients with asneeded treatment compared with patients under maintenance treatment. 2 In the PRACTICAL study, NO levels were also greater after 1 year of follow-up in patients switched from ICS treatment at baseline to as-needed ICS-FOR treatment. 4 This suggests that loss of control of airway inflammation can occur with long-term as-needed treatment and contribute to worsening of asthma symptoms.…”
mentioning
confidence: 95%
“…1 This strategy resulted in reducing the risk of severe exacerbation but with limited evidence of improvement in both symptom control and lung function compared with daily low-dose ICS treatment. 2 Despite the unquestionable strength of evidence provided by randomized controlled trials on the efficiency of the as-needed strategy, we are not absolutely certain about the effectiveness of this strategy when applied to real-world clinical practice in low-and middle-income countries, for these reasons:…”
mentioning
confidence: 99%